PROGRAM LIFE SKILLS DALAM BERWIRAUSAHA BUDIDAYA ITIK PETELUR DI SKB KABUPATEN KAUR - nipriansyah nipriansyah; Connie Connie (Manajer Pendididikan, 2019)
Abstract: the goal of this study are to describe the life skills program in increasing the ability of laying ducks cultivation entrepreneurship. The research method used are qualitative descriptive. The technique of data collection used observation, interview and documentation. The subjects of the study are head of SKB Kaur regency, educator and residents who learned in life skill program The result of this research shows the implementation of life skill program of duck laying cultivation is well and through the planning stage, and stages of evaluation, there are some supporting factors and obstacle factors in the implementation of life skills program of laying ducks, then Benefits of life skills program of laying duck can improve the ability of entrepreneurship cultivation of duck laying. Furthermore, the recommendation of life skill of laying ducks cultivation can improve the ability of entrepreneurship well.Keywords: Life Skills Program, SKB, Laying ducks Cultivation